2017
DOI: 10.1158/1940-6207.capr-17-0015
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Suppresses Inflammation-Driven Colorectal Cancer in Mice

Abstract: Intestinal cyclic guanosine monophosphate (cGMP) signaling regulates epithelial homeostasis and has been implicated in the suppression of colitis and colon cancer. In this study, we investigated the cGMP-elevating ability of the phosphodiesterase-5 (PDE5) inhibitor sildenafil to prevent disease in the azoxymethane/dextran sulfate sodium (AOM/DSS) inflammation-driven colorectal cancer model. Treatment of mice with sildenafil activated cGMP signaling in the colon mucosa and protected against DSS-induced barrier … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 43 publications
4
51
0
1
Order By: Relevance
“…We detected PDE5 in two of five NSCLC cell lines examined, but the levels were comparable to NHAEC. The PDE5 selective inhibitor, sildenafil has also been reported to inhibit tumorigenesis in an inflammation-driven model of colon cancer, which suggests a potentially important role of PDE5 in tumorigenesis [ 47 ]. However, the abundance of PDE10 in tumor cells may limit the sensitivity of tumor cells to PDE5 inhibitors, whereby combined treatment with PDE5 and PDE10 inhibitor or treatment with a dual PDE5/10 inhibitor may hold greater promise as a therapeutic strategy [ 33 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We detected PDE5 in two of five NSCLC cell lines examined, but the levels were comparable to NHAEC. The PDE5 selective inhibitor, sildenafil has also been reported to inhibit tumorigenesis in an inflammation-driven model of colon cancer, which suggests a potentially important role of PDE5 in tumorigenesis [ 47 ]. However, the abundance of PDE10 in tumor cells may limit the sensitivity of tumor cells to PDE5 inhibitors, whereby combined treatment with PDE5 and PDE10 inhibitor or treatment with a dual PDE5/10 inhibitor may hold greater promise as a therapeutic strategy [ 33 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, exisulind prevented colorectal polyp formation in patients with familial adenomatous polyposis (FAP) over 24 months [ 243 , 244 ]. Moreover, it has been demonstrated that exisulind inhibited azoxymethane-induced colon carcinogenesis in rats [ 201 ] and sildenafil suppressed polyp formation and inflammation in mice treated with azoxymethane/dextrane sulfate sodium [ 245 ], highlighting the chemopreventive role of PDE5 inhibition [ 246 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, the immunomodulatory effects of PDE5 inhibitors have been suggested to be associated with an anticancer effect, which was first shown by Serafini et al 35 and then further confirmed by other researchers in studies conducted on mice. 17,36,37 Second, Zhu et al 38 and Wang et al 39 conducted experiments in vitro and found that PDE5 inhibitors induced apoptosis, inhibited cell proliferation, and promoted differentiation in colonic epithelium by activating the cGMP/ protein kinase G II pathway. 38,39 In addition, a range of results in vitro showed that PDE5 was related to increased cancer treatment sensitivity through inhibiting resistance to some commonly used cancer drugs (5-fluorouracil and doxorubicin) or enhancing tumor permeability via effects on the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%